Nutrition education about breakfast and healthy snacks to prevent anemia in teenagers at SMK Dharma Wanita Gresik - Desty Muzarofatus Sholikhah; Pemta Tiadeka (Community Empowerment, 2024)
Gresik Regency, with its rapid industrial growth, faces a high rate of anemia among adolescents, particularly in Kebomas District. Initial studies indicate that skipping breakfast and consuming unhealthy snacks are primary contributors. This community service program aimed to increase adolescent knowledge about the importance of healthy breakfasts and nutritious snacks to prevent anemia. Through structured nutrition education, the program sought to modify adolescent eating habits. Methods included delivering interactive nutrition education materials to SMK Dharma Wanita Gresik students. Evaluation results showed a significant rise in participants' balanced nutrition knowledge, with the percentage of participants demonstrating good knowledge increasing from 6.1% to 79.6%.